pNPs-CapsNet: Predicting Neuropeptides Using Protein Language Models and FastText Encoding-Based Weighted Multi-View Feature Integration with Deep Capsule Neural Network - Shahid Akbar; Ali Raza; Hamid Hussain Awan; Quan Zou; Wajdi Alghamdi; Aamir Saeed (2025)
Neuropeptides (NPs) are critical signaling molecules that are essential in numerous physiological processes and possess significant therapeutic potential. Computational prediction of NPs has emerged as a promising alternative to traditional experimental methods, often labor-intensive, time-consuming, and expensive. Recent advancements in computational peptide models provide a cost-effective approach to identifying NPs, characterized by high selectivity toward target cells and minimal side effects. In this study, we propose a novel deep capsule neural network-based computational model, namely pNPs-CapsNet, to predict NPs and non-NPs accurately. Input samples are numerically encoded using pretrained protein language models, including ESM, ProtBERT-BFD, and ProtT5, to extract attention mechanism-based contextual and semantic features. A differential evolution-based weighted feature integration method is utilized to construct a multiview vector. Additionally, a two-tier feature selection strategy, comprising MRMD and SHAP analysis, is developed to identify and select optimal features. Finally, the novel capsule neural network (CapsNet) is trained using the selected optimal feature set. The proposed pNPs-CapsNet model achieved a remarkable predictive accuracy of 98.10% and an AUC of 0.98. To validate the generalization capability of the pNPs-CapsNet model, independent samples reported an accuracy of 95.21% and an AUC of 0.96. The pNPs-CapsNet model outperforms existing state-of-the-art models, demonstrating 4% and 2.5% improved predictive accuracy for training and independent data sets, respectively. The demonstrated efficacy and consistency of pNPs-CapsNet underline its potential as a valuable and robust tool for advancing drug discovery and academic research.